Two Extensions of Diametrically Contractive Mappings. (11th March 2020) - Sankar Raj, V.; Piramatchi, T.
Abstract: In this manuscript, we introduce two extensions of diametrically contractive mappings and provided sufficient conditions for the existence of a generalized fixed point, called the best proximity point, for such mappings. Our results generalize the fixed point theorems of Xu, Dhompongsa, and Yingtaweesittikul.